Pengaruh Penggunaan Media Blooket dalam Meningkatkan Hasil Belajar Siswa Kelas X pada Mata Pelajaran Sejarah Hindu-Budha - Matitaputty, Jenny K,; Maysuri, Tama; Lokollo, Helsti (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of using Blooket learning media on the learning outcomes of 10th-grade students in the Hindu-Buddhist History subject at SMAN 4 Ambon. The study used a quantitative approach with a true experimental design method through a pretest–posttest control group design. The sample consisted of two classes, namely a control class using the lecture method and an experimental class using Blooket media, each with 30 students. The research instrument was a multiple-choice test given before and after the treatment. Data analysis was carried out by calculating the average value and N-Gain. The results showed that the increase in learning outcomes in the experimental class was higher than in the control class. The N-Gain value of the control class was in the medium category (0.53), while the experimental class reached the high category (0.70). These findings indicate that the use of Blooket media is more effective in improving student learning outcomes. Thus, digital game-based learning media can be an effective alternative to improve student learning outcomes in history learning.